Meningkatkan Minat Belajar Pendidikan Agama Islam (PAI) Melalui Model Problem Based Learning (Studi Kasus di Kelas XI MIPA I SMAPLUS Ar-Raudhah Purwakarta) - Kinanthi, Diah Ayu Sekar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Teachers hold an important role in fostering the learning interest of students so that the learning atmosphere becomes comfortable and the lesson material is easier to understand. One passable strategy is to use learning media that are interesting and appropriate to the material being taught. Media has an important role especially for lower grade primary school students, because at this stage their abstract thinking ability has not developed optimally so the material needs to be visualized in a concrete form. From a psychological point of view, learning media aid cognitive development while providing meaningful learning experiences. The implications of media use impact not only students, but also teachers as well as the dynamics of the learning process in the classroom. In designing learning media, several principles are noteworthy, namely: (1) media should be simple, clear, and easy to understand; (2) the medium is tailored to the subject being taught; (3) media should not be too complicated so as not to confuse students; (4) media should be made of simple and easily obtainable materials, without diminishing their function as well as their meaning; (5) Media can be models, drawings, charts, or other practical and affordable visual forms. Additionally, the application of the Problem Based Learning (PBL) model can be an effective alternative. This model encourages students to actively engage in the learning process through solving real problems relevant to daily life. PBL not only increases students’ learning interest through critical thinking challenges, but also provides a space for collaboration among learners. If combined with the right learning medium, the application of PBL will increasingly make it easier for students to grasp abstract concepts concretely, so their learning outcomes and learning motivation can be significantly improved.